Populist Traits in Don Juan José de Austria’s Propaganda against J. E. Nithard: 1668–1669 - Sánchez-Marcos, Fernando (Populismo y propaganda: entre el presente y el pasado, 2020)
The pamphlet war between Juan José de Austria (or John of Austria the Younger or John Joseph of Austria) and J. E. Nithard (the favourite of the regent Mariana of Austria) is a milestone in the history of political propaganda in Baroque-period Spain. Juan José succeeded in disseminating attractive messages, such as “clean hands”, and unfeasible promises that pandered to the ears of sectors of urban society excluded from power. This paper is based on my own studies and I analyse the information provided by the growing body of available sources. Special attention is paid to the interpretative framework proposed by H. Hermant (2012), without losing sight of the experience of contemporary populism.